Hubungan Kualitas Laba, Profitabilitas, Dan Corporate Social Responsibility Terhadap Return Saham - Marbun, Ruth Stephany; Suhartini, Dwi (Universitas Gorontalo, 2024)
This research aimed to analyze and measure the relationship between earnings quality, profitability, and corporate social responsibility on stock returns of food and beverages sector companies in 2020-2022. The population in this study obtained 30 companies with a sampling technique using purposive sampling so that 54 companies were obtained as samples. The data analysis technique used multiple linear regression analysis. The results of this study indicate that earnings quality and return on investment affect the disclosure of stock returns. While corporate social responsibility cannot affect the disclosure of stock returns. This research is expected to provide an overview of what stock return disclosure is influenced by so that it can be used by companies for evaluation and decision making.